HISTORY OF FIQH - Hafizov Najmiddin (Galaxy International Interdisciplinary Research Journal, 2021)
The caliphate of the science of jurisprudence emerged during the ijtihad movement during the time of the Rashidins and their successors. The Companions used to ask each other for fatwas on new issues. Those of them who were mujtahids sought the Shari'ah ruling on this issue from the verses of the Qur'an and the hadiths. Then they would make comparisons or do ijtihad with Ray accordingly.